Hydatid cyst of the pancreas: A case report and brief review - İbrahim MASOODI,; Ghulam NABI,; Rakesh KUMAR,; Mushtaq Ahmad LONE,; Bilal Ahmad KHAN,; Khalid NASEER AL SAYARI, (Turkish Journal of Gastroenterology, 2019)
-